2022
DOI: 10.1021/acs.energyfuels.2c01815
|View full text |Cite
|
Sign up to set email alerts
|

Intensified Carbon Dioxide Hydrate Formation Kinetics in a Simulated Subsea Sediment: Application in Carbon Capture and Sequestration

Abstract: To achieve the United Nations Climate Change Conference (COP-26) targets of net zero carbon emissions, hydrate-based carbon dioxide (CO 2 ) capture and sequestration (CCS) can be considered one of the potential sustainable technologies. However, the sluggish kinetics of CO 2 hydrate formation in the saline subsea environment and the nonecofriendly nature of the existing additives (kinetic promoters) are the major challenges. Therefore, to intensify the kinetics, the performance of the biocompatible hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…Cai et al 38 showed that L-Met possessed an excellent promotion effect on the formation of CO 2 hydrate, with CO 2 gas uptake reaching up to 0.145 mol CO 2 /mol H 2 O in 1000 min at the concentration of 0.1 wt %. Gautam et al 39 found that adding 0.5 wt %L-leucine to freshwater resulted in CO 2 gas uptake of 0.10 mol CO 2 /mol H 2 O, which was four times higher than the system without a promoter. In addition, L-isoleucine and L-tryptophan have also been proved to be kinetic promoters for improving CO 2 hydrate kinetics.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cai et al 38 showed that L-Met possessed an excellent promotion effect on the formation of CO 2 hydrate, with CO 2 gas uptake reaching up to 0.145 mol CO 2 /mol H 2 O in 1000 min at the concentration of 0.1 wt %. Gautam et al 39 found that adding 0.5 wt %L-leucine to freshwater resulted in CO 2 gas uptake of 0.10 mol CO 2 /mol H 2 O, which was four times higher than the system without a promoter. In addition, L-isoleucine and L-tryptophan have also been proved to be kinetic promoters for improving CO 2 hydrate kinetics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cai et al showed that l -Met possessed an excellent promotion effect on the formation of CO 2 hydrate, with CO 2 gas uptake reaching up to 0.145 mol CO 2 /mol H 2 O in 1000 min at the concentration of 0.1 wt %. Gautam et al found that adding 0.5 wt % l -leucine to freshwater resulted in CO 2 gas uptake of 0.10 mol CO 2 /mol H 2 O, which was four times higher than the system without a promoter. In addition, l -isoleucine and l -tryptophan have also been proved to be kinetic promoters for improving CO 2 hydrate kinetics. Thus, in our study, we mainly focus on how low-dose THF (less than 1.0 mol %) can improve the kinetics of CO 2 hydrate formation and aim to examine if there is a synergistic effect when low-dose THF is coupled with a type of amino acid, l -Met, as a KHP for CO 2 hydrate.…”
Section: Introductionmentioning
confidence: 99%
“…112−116 However, current research has shown that only some amino acids (e.g., L-methionine, L-tryptophan, and L-leucine) can considerably improve the formation kinetics of the CO 2 hydrate. 117,118 Presently, why only some hydrophobic amino acids can effectively promote the formation of the CO 2 hydrate remains unclear.…”
Section: Promotion Mechanism Of Khasmentioning
confidence: 99%
“…Notably, among the different amino acids, only the L-methionine, L-tryptophan, and Lleucine can promote the CO 2 hydrate formation. 117,118 Although the reason for this phenomenon remains unclear, the promotion mechanism must be elucidated because it is conducive to finding more effective promoters. Table 7 summarizes the experimental conditions of these studies.…”
Section: Surfactants + Amino Acidsmentioning
confidence: 99%
“…The moles/rate calculations during hydrate formation were similar to our previous studies. 29,31 The gas uptake or mole of gas consumed during the hydrate growth phase was calculated using eq 1 and presented as a mole of gas consumed per mole of water in all the figures below.…”
Section: Mole Calculation For Hydrate Formationmentioning
confidence: 99%